Análise espacial da produtividade de café em Minas Gerais (2002-2017) - Bernardes, Renan Serenini (2019)
Brazil is the world’s largest coffee producer. For the last 20 years, has been responsible by approximately one third of world production. In Brazil, the most prominent state is Minas Gerais, which, according to estimates by CONAB - National Supply Company,In 2018 it produced over 53% of all coffee produced in the country. Considering the relevance of coffee and the state of Minas Gerais in the context, this paper aims to analyze thes patial distribution of productivity (measured by the ratio of coffee production over the harvested area) of the coffee in MG from 2002 to 2017 and to verify the evolution of production and productivity over the period. Speciﬁcally, the spatial distribution was analyzed through the division of the state in immediategeographicregions,thenewregionaldivisionpublishedbyTheBrazilianInstitueof Geography and Statistics (IBGE), in 2017. To achieve the objective, the series of production, productivity and harvested area were analyzed, verifying the existence of dependence between the regions and clusters of high or low productivity over the years.Spatial dependence was estimated using Moran’s I statistics and cluster indication or space outliers was veriﬁed by the local Moran’s I. The results indicated that the coffee productivity in Minas Gerais as a whole has been increasing in recent years. Some regions that had small areas of coffee stopped producing and other regions, which had large areas, but with low productivity levels, increased its productivity,indicating a concentration movement of production. It was identiﬁed that the spatial dependence of productivity was more signiﬁcant in the ﬁrst period (2002 to 2009) than in second (2010 to 2017). Some high productivity clusters have been identiﬁed, showing most signiﬁcant in the ﬁrst period. The results of the work can serve as subsidy for new research, implementing variables associated with coffee productivity, as well assupport for policy making in the sector.